EFEKTIFITAS PEMBERIAN OBAT PENURUN PANAS PADA BAYI YANG DIBERIKAN IMUNISASI DPT DAN CAMPAK DI PUSKESMAS PEMULUTANKABUPATEN OGAN ILIR TAHUN 2020 - Desy anggraini; Dwi Apriani (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2020)
Immunization is an effort to provide protection for infants and children by inserting vaccines into the body sothat the body makes anti-substances to prevent certain diseases.The purpose of this study was to determine the effectiveness of giving hot medicine to infants who were givenDPT and measles immunization at Puskesmas Pemulutan Ogan Ilir Regency in 2020.This research is a quasi-experimental research with a pre-post-test group design design that is research conductedby dividing the subject into 2 groups, namely experiment and control. The first observation (pre-test) that allowsto test changes that occur after the treatment with a post-test by providing interventions to respondents who willtake action on health education related to the provision of heat medication to immunized children. Comparingbefore and after being given health education without a comparison group.It was found that the average of the control group after being given a heat retarding drug was 94.10, while theaverage of the treatment group after being given a heat retarding was 56.80 it can be concluded that there was asignificant difference with p 0.003 (p <0.05) , 5 ml compared with the control group. This means that theprovision of heat-reducing drugs with a dose of 0.5 ml after injection of immunization 2 hours afterwards greatlyaffects the body temperature of babies who are immunized DPT and Measles